Collaboration evaluation methodology for experience capitalization in industrial processes. Issue 13 (2019) - González, D. Meléndez; Coudert, T.; Geneste, L.; Valroger, A. De
Abstract: Collaboration is a key factor that encourages an efficient running of industrial processes. The measurement of the collaboration performance is necessary to allow experience capitalization and reuse in order to support decision making about efficient collaborations in future processes. This article describes a proposition of collaboration and performance evaluation methodology in industrial processes for experience capitalization. For this purpose, a collaboration model is introduced in order to develop an evaluation methodology. Finally, a case study applied to the aeronautical domain is presented to illustrate the methodology and validate the proposals.